The Influence of Working Capital, Cash Turnover, and Receivables Turnover on the Profitability of PT Pegadaian Syariah Indonesia (2019-2023) - Ekanitami Febriyanti; Intan Puspitasari; Agus Saur Utomo (Eduvest - Journal of Universal Studies, 2025)
This study examines the influence of working capital turnover, cash turnover, and receivables turnover on the profitability of PT Pegadaian Syariah Indonesia during the 2019–2023 period. As a Sharia-compliant financial institution, efficient financial management ensures liquidity, operational sustainability, and profitability. Despite existing research on these variables in conventional sectors, limited studies focus on Islamic financial institutions, creating a gap that this study aims to address. The research employs a quantitative approach, using secondary data from the company’s annual financial reports. Multiple linear regression analysis tests the relationship between the independent variables (working capital, cash, and receivables turnover) and the dependent variable (profitability, measured by Return on Assets, ROA). Findings reveal that all three variables significantly and positively impact profitability. Working capital turnover has the most substantial effect (coefficient: 0.325), followed by cash turnover (0.274) and receivables turnover (0.208). Efficient management of these components enhances operational efficiency, liquidity, and cash flow, thereby boosting profitability. The study underscores the importance of optimizing working capital, proactive cash management, and stricter receivables policies for PT Pegadaian Syariah Indonesia. It contributes to the literature on Islamic financial management and offers practical insights for improving profitability. Future research could expand by incorporating macroeconomic factors or comparative analysis with other Islamic financial institutions.